Heterologous expression of the plant cysteine protease bromelain and its inhibitor in Pichia pastoris. (29th November 2016) - Luniak, Nora; Meiser, Peter; Burkart, Sonja; Müller, Rolf
Abstract : Expression of proteases in heterologous hosts remains an ambitious challenge due to severe problems associated with digestion of host proteins. On the other hand, proteases are broadly used in industrial applications and resemble promising drug candidates. Bromelain is an herbal drug that is medicinally used for treatment of oedematous swellings and inflammatory conditions and consists in large part of proteolytic enzymes. Even though various experiments underline the requirement of active cysteine proteases for biological activity, so far no investigation succeeded to clearly clarify the pharmacological mode of action of bromelain. The potential role of proteases themselves and other molecules of this multi‐component extract currently remain largely unknown or ill defined. Here, we set out to express several bromelain cysteine proteases as well as a bromelain inhibitor molecule in order to gain defined molecular entities for subsequent studies. After cloning the genes from its natural source Ananas comosus (pineapple plant) into Pichia pastoris and subsequent fermentation and purification, we obtained active protease and inhibitor molecules which were subsequently biochemically characterized. Employing purified bromelain fractions paves the way for further elucidation of pharmacological activities of this natural product. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:54–65, 2017